ANALISIS PENGARUH KINERJA KEUANGAN, KINERJA OPERASIONAL, BIAYA EKUITAS DALAM PENGUNGKAPAN EMISI KARBON UNTUK MENCIPTAKAN NILAI PERUSAHAAN - Cholida Cholida; Warsito Kawedar (Diponegoro Journal of Accounting, 2020)
The purpose of this study was to examine the effect of financial performance, operational performance and cost of equity on the disclosure of carbon emissions and company value in manufacturing companies in Indonesia. The population in this study consisted of manufacturing companies on the Indonesia Stock Exchange in the period 2015-2017 which published an annual report and made carbon emissions disclosures. Samples were taken using a purposive sampling method. The total sample in this study is 15 companies each year, selected by purposive sampling method and using secondary data. This study uses multiple regression analysis for hypothesis testing. The results of this study indicate that only operational performance has a significant positive effect on disclosure of carbon emissions. And only financial performance has a significant positive effect on firm value.